Consumer Market Research for Mathsando - Camela Putri Mahmouda; Adinda Esa Tinaka; Sasikirana Zahra Maheswari (Journal of Economic and Business Analysis, 2024)
Mathsando is the result of culinary innovation that combines mathematical sciences with Japanese fruit sando cuisine. This research was conducted to determine the potential and market interest in product innovation to reduce any risk of business failure that might occur. The method used in this research is descriptive with a qualitative approach. Data was obtained by distributing questionnaires to 70 respondents located on Java Island. The data were analyzed using trend analysis, similarity analysis, contradiction analysis, and odd groupings analysis. The results of this study show that trend analysis includes age, gender, occupation, income, and taste preferences. Similarity analysis includes knowing fruit sando, having bought fruit sando, fruit preference as fruit sando filling, things that influence buying Mathsando, and the desire to recommend Mathsando. Meanwhile, contradiction analysis and odd groupings analysis were not found in this study. The conclusion obtained from this study is that Mathsando has significant market potential. However, further marketing efforts are needed to capitalize on this trend and increase market penetration.